Information technology. International standardized profile TAnnnn. Connection-mode transport service over connectionless-mode network service. TA1111/TA1121 profiles including subnetwork-dependent requirements for X.25 packet-switched data networks using virtual calls Part 5, (15th March 1994) - British Standards Institution,
No abstract available